A 62 YEARS OLD WOMAN WITH RECURRENT DEPRESSIVE DISORDER, CURRENT EPISODE MODERATE, WITH SOMATIC - Hanif Fakhruddin (Fakultas Kedokteran Universitas Lampung, 2015)
Depressive disorder is a disorder in which there is a change in the emotional condition, motivation, function and motor behavior, and even cognitive. Female, 62 years old, with chief complain of moody, lost of interest, difficulty of sleeping, anxiety, restlessness, and feel hatred of her mother. Physhical examination found epigastric pain, from psychiatry status patient appearance was good, moody, often bowing her head and cry. The affective was depressive, talked less velocity with pressure, volume decrease, had idea of guilt, and insight was 5. Pasient diagnosed with axis I: recurrent depressive disorder, current episode moderate, with somaticsymptoms; axis II: not found; axis III: dyspepsia syndrome; axis IV: family problems; axis V: GAF HLPY: 80-71, Current GAF: 60-51. Pharmacotherapy treated with fluoxetine 1 x 20 mg, clobazam 2 x 5 mg, 2 x 150 mg ranitidine, and interpersonal psychotherapy. Depressive disorder patients is due to family problems with her biological mother. Based on GAF scores indicate good prognosis in this case. [J Agromed Unila 2015; 2(1):1-5]Keywords: moderate episode, recurrent depressive disorder, somatic symptoms